Experimental and numerical evaluation of reinforced dry-stacked concrete masonry walls. (March 2019) - Martínez, Marcos; Atamturktur, Sez
Abstract: In dry-stack concrete masonry systems, masonry units are laid without mortar joints, reducing the cost and the time required for construction. Despite these advantages, mortarless construction has not been widely implemented, which is attributed to the fact that the behavior of dry-stack masonry wall systems is not yet fully understood. To help fill this knowledge gap, experimentally-validated finite element models of dry-stacked concrete masonry walls have been developed to investigate the effect of various design parameters (e.g., unit and grout compressive strength, yield strength, and reinforcement and grouting ratios) on the out-of-plane load-carrying capacity of the walls. The present paper reports the findings obtained from this combined experimental and numerical study to support the development of future design guidelines for dry-stack concrete masonry systems. Highlights: Out of plane behavior of dry-stacked concrete masonry wall systems is evaluated through a combined experimental and numerical study. Finite element model is capable of predicting the behavior of dry-stacked concrete masonry wall with a good agreement with experiment test in the laboratory. Parametric analysis is performed to describe the behavior of dry-stacked walls under untested scenarios and configurations.